Comparative Study of Explosive Strength among Long Jumpers and Sprinters - Bhavani Rajeshwari, S. (International Journal of Psychosocial Rehabilitation, 2010)
The long jump is a track and field event in which athletes combine speed, strength and agility in an attempt to leap as far as possible from a take-off point. Along with the triple jump, the two events that measure jumping for distance as a group are referred to as the "horizontal jumps". This event has a history in the ancient Olympic Games and has been a modern Olympic event for men since the first Olympics in 1896 and for women since 1948.Sprinting is running over a short distance at the top-most speed of the body in a limited period of time. It is used in many sports that incorporate running, typically as a way of quickly reaching a target or goal, or avoiding or catching an opponent.Research Objective The objective of this study to determine the Explosive Strength in the legs of Long Jumpers and Sprinters.Review of Literature Matthews & Comfort (2008) state, it involves “the use of contrasting loads to elicit an acute enhancement in power output”Prof.Rajesh Kumar and et.al (2009) has studied about the Speed, Agility and Power among Long Jumpers and Sprinters of Junior Colleges. It is concluded that Long Jumpers are good in speed and power and Sprinters are good agility.Methodology The sample for the present study consists of 30 Male Long Jumpers and 30 Male Sprinters of Junior Colleges. To assess the Explosive Strength Standing Broad Jump Test was conducted among Long Jumpers and Sprinters.